1986
DOI: 10.1111/j.1600-0404.1986.tb04607.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary non-Hodgkin's lymphomas of the CNS

Abstract: This paper reports on 10 patients (4 male, 6 female) with primary non-Hodgkin's lymphomas of the brain (CNS-NHL--mean age 46.8 years, mean postdiagnostic survival 10 months). Pathological CSF (cerebrospinal fluid) was found in all 8 patients examined (positive cytology in 7/8 cases). Solitary tumors, diffuse periventricular infiltration or diffuse cerebral infiltration were demonstrated in cerebral computer-assisted tomography (CAT). Angiographical findings were unspecific. The histologic subtypes were lymphop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

1990
1990
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(47 citation statements)
references
References 51 publications
2
44
1
Order By: Relevance
“…8 in our study). Bogdahn et al (1986), Miller et al (1994) and Villegas et al (1997) reported a better survival with low-grade histology. Thus, local and symptom-oriented therapy may be the best approach for at least some patients with low-grade PCNSL, considering the risk of late neurotoxicity after intensive PCNSL treatment.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…8 in our study). Bogdahn et al (1986), Miller et al (1994) and Villegas et al (1997) reported a better survival with low-grade histology. Thus, local and symptom-oriented therapy may be the best approach for at least some patients with low-grade PCNSL, considering the risk of late neurotoxicity after intensive PCNSL treatment.…”
Section: Discussionmentioning
confidence: 94%
“…In the series of 10 patients reported by Bogdahn et al (1986), five patients (three males, two females, age 27-60 years) had a lowgrade histology: four had a lymphoplasmacytoid immunocytoma and one had an unclassified lymphoma. Remarkably, cerebellar localization and neoplastic cells in the CSF were present in each of the three patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Working Formulation 79% would have been classified as diffuse large-cell lymphoma in the REAL classification, whereas only 48.8% would have been interpreted as such in the updated Kiel Classification [28]. Perhaps this discrepancy explains in part the fact that some authors find a correlation with survival [20,28,51,52] while others do not [12,53]. Another classification awaited from the WHO may solve current problems [24].…”
Section: Histological Classificationmentioning
confidence: 85%
“…Magnetic resonance (MR) images of MLshow two features similar to those of other brain tumors: expanding mass lesions and gadolinium (Gd)-enhancing lesions (3)(4)(5). Only a few cases with unusual MRIfindings are reported; these showeither Gd-enhancingdiffuse white matter lesions without mass effect (4,6) or non-Gd-enhancing "mass" lesions (7)(8)(9). Here we report a patient with T-cell lymphoma showing both non-Gd-enhancing and diffuse T2-high signal intensity lesions in the cerebral white matter.…”
Section: Introductionmentioning
confidence: 97%